Analisa Pengaruh BOPO terhadap ROE pada PT. Bank Negara Indonesia (BNI), Tbk. - Puji Muniarty; Suci Tricahyanti (Universitas Bumigora, 2022)
This study aims to determine and analyze the effect of BOPO risk on ROE at PT. Bank Negara Indonesia (BNI). The research method used is associative quantitative research. The sample of this study consists of balance sheets and income statements for 10 years from the period 2011 - 2020 with the sampling technique used is purposive sampling. The analytical tools used are classical assumptions, simple linear regression, Coefficient of Determination and Simple Correlation, and Partial Test which aims to analyze the relationship between BOPO variables and ROE using SPSS v software. 23. The results of this study indicate that BOPO has no effect on ROE at PT. Bank Negara Indonesia, Tbk.